Increasing the Quality of Gendola Fruit Syrup as a Healthy Drink - Nur Aini Dewi Purnamasari; Ganet Eko Pramukantoro; Muhammad Dzakwan (MITRA: Jurnal Pemberdayaan Masyarakat, 2020)
Gendola herbal syrup is a solution in the form of syrup containing gendola as an active substance that is dissolved in the syrup component. Gendola syrup has a high betalain antioxidant content, and is beneficial for improving health. Betalain antioxidant content is easily damaged due to the influence of air, humidity, and temperature, causing the red color of the gendola to fade. The implementation of this project aimed to help improve the quality of Gendola syrup and provide training to partners so that they were able to market Gendola syrup products online. This project was implemented in productive community groups, UDHerba Puspitasari in Mlandangan Rt 02 Rw 08, Mandan Village, Sukoharjo District Sukoharjo Regency to make them able to produce and market herbal processed products. Based on observations of the results achieved, our partners were able to produce herbal syrup, although it was still limited, the quality was not good, and it did not yield profits. The methods implemented in this program included: 1) provide training for making Gendola syrup with encapsulation methods; 2) provide equipment that can support the production process; 3) provide online marketing training. The results obtained in this community-service activity contributed siqnificantly to UD Herba Puspitasari in their efforts of producing high-quality Gendola syrup and marketing the products online.